Assessing the implementation of the IMF's 2007 surveillance decision - Robert Lavigne; Garima Vasishtha (Bank of Canada, 2009)
The International Monetary Fund (IMF) recently adopted the 2007 Decision on Bilateral Surveillance Over Members' Policies, a landmark reform that modernizes the general principles of IMF surveillance. However, support for the reform was not unanimous, and doubts have been expressed about how the Decision would be applied in practice. The authors assess the first year of the Decision's implementation in Article IV reports. Using a questionnaire based on the key aspects of the Decision, they evaluate Article IV reports published before and after the adoption of the new Decision for a set of 24 countries. The authors find that the Decision has significantly increased the overall quality of Article IV reports, with improvements noted in emerging-market, advanced, and developing countries. Bilateral surveillance is more focused on external stability and core macroeconomic policies. Exchange rate analysis, in particular, has improved significantly. The authors note, however, that the integration with multilateral surveillance remains relatively weak and that cross-country spillovers still do not receive sufficient attention. Moreover, while most reports examine domestic stability in some detail, the link between domestic stability and external stability is not adequately analyzed. On the issue of the evenhanded application of the Decision, the authors conclude that implementation has been broadly similar across country income groups, although differences remain for specific aspects of the Decision.
Keywords: F33; 330; International topics; Internationale Wirtschaftsbeziehungen; Internationales Wirtschaftsrecht; Internationale Wirtschaftsorganisation